Penerapan Tax Planning atas Pajak Penghasilan Badan pada CV. Wira Arya Sejahtera - Dina Putri Nadiati; Syamsul Bahri Arifin; Desi Ika (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the implementation of tax planning on corporate income tax at CV Wira Arya Sejahtera to optimize tax obligations legally and in compliance with applicable tax regulations. The research adopts a qualitative descriptive approach using a case study design. Data were collected from the company’s 2023 financial statements and Annual Tax Returns (SPT). The analysis focuses on identifying opportunities for tax efficiency through deductible expense optimization, appropriate accounting treatment, and legitimate tax-saving strategies under Indonesian tax law. The findings reveal that through effective tax planning, the company successfully reduced its Taxable Income (PKP), resulting in a decrease in the Corporate Income Tax (PPh Badan) payable from IDR 200,119,828 to IDR 162,284,665. This adjustment led to total tax savings of IDR 37,835,163. The study concludes that proper tax planning not only contributes to lowering tax expenses but also strengthens the company’s financial performance and compliance posture. Therefore, systematic and lawful tax planning should be continuously applied as part of the company’s financial management strategy to achieve sustainable efficiency.